UNDERSTANDING RADIO'S ROLE IN RURAL ENVIRONMENTAL AWARENESS IN OGONI LAND - Nwankwo, Chinedu Okwudili; Okafor, Amara Nkechi; Adeyemi , Biodun Oluwaseun (International Research Journal of Arts and Communication, 2024)
The study focused on the imminent undermining of the remediation work on oil-impacted sites in Ogoni land in the event of message misinterpretation in the communication process between HYPREP and Ogonis occasioned by negative perception of the radio programme in focus. Hence, this study examined the awareness and knowledge of Eleme people on radio programming about rural environment issues in Ogoniland. The study anchored on the individual difference theory, which added validation to the findings. The study adopted the survey research design and a mixed method to collect both quantitative and qualitative data. The population for the study is that part of the active audience of the Ogoni clean-up show on 93.7 FM from which the researcher got data for the research. The population was gotten from the active audience of the Ogoni clean-up show on Rhythm 93.7 FM in Eleme Local Government Areas of Rivers State. The 2006 census figures for Port Harcourt 338,552 (FGN Official Gazette, 2009) and a 2.7% growth rate put the figure at 914,090 as at 2022. A total number of 385 respondents were selected as the sample size for this study using Meyer determinant table. The multi-stage cluster sampling technique was adopted to select the participants for sampling. The quantitative data collated from the questionnaire were presented in a frequency tabular form, whereas, the explanation building technique was used to analyze the qualitative data from the focus group discussion. Findings revealed that Eleme residents were not aware of the “Ogoni clean-up show on Rhythm 93.7 FM”. This means that the programme’s popularity was not overwhelming among Elelme residents. The study recommended that an aggressive promotion should be done to popularize the programme for audience members to be aware and regularly follow-up the programme; sensitize the audience on the main focus and motif of the programme in order to mobilize audience participation that will make the programme effective and useful for rural development.